2000
DOI: 10.1520/jfs14875j
|View full text |Cite
|
Sign up to set email alerts
|

Suicide: A Ten-Year Retrospective Study

Abstract: Suicide is a complex phenomenon associated with psychological, biological, and social factors, claiming approximately 30,000 lives each year in the United States. We retrospectively reviewed all cases referred to the Medical Examiners' Office/Forensic Pathology Section at the Medical University of South Carolina from January 1988 to December 1997. The cases of suicide totaled 678. All of the cases were analyzed as to age/race/sex, method of suicide, time of year, and toxicological results. Files were also revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 9 publications
4
39
3
2
Order By: Relevance
“…As a matter of fact, the excess of the number of girls in the SIS data (Table 8) was also reflected in our study. In many studies, the rate of completed suicide were reported to be higher in men [22,23,26,[30][31][32][33][34][35][36] whereas the rate of attempting suicide to be higher in women [18,[36][37][38][39]. The rate of completed suicide is three times higher in men than women but when the rate of attempting suicide is taken into account, the rate seems to be reversed in favor of women [40].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, the excess of the number of girls in the SIS data (Table 8) was also reflected in our study. In many studies, the rate of completed suicide were reported to be higher in men [22,23,26,[30][31][32][33][34][35][36] whereas the rate of attempting suicide to be higher in women [18,[36][37][38][39]. The rate of completed suicide is three times higher in men than women but when the rate of attempting suicide is taken into account, the rate seems to be reversed in favor of women [40].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors underline the meaning of widowhood (Lantz, 2001;Erlangsen et al, 2003), while others of being separated, divorced or, more comprehensively, of living alone (Florio et al, 1997). The methods used to commit suicide are tightly related to their availability and accessibility, to their image in society and to the intervention of commonplace features: some studies report hanging as the most used method (Isometsä et al, 1997;Purcell et al, 1999;Harwood et al, 2000;Byard et al, 2004), others (Osuna et al, 1997;Tadros and Salib, 2000) jumping, drowning or drug overdose, while in the United States the use of fire-arms (Bennett and Collins, 2001; is reported as being the most common.…”
Section: Introductionmentioning
confidence: 99%
“…However, in western civilizations, burning is not a preferred method of homicide [13,14]. In Turkey, homicidal burns induced with paint thinner are after sharp/blunt trauma and firearms the third most frequent cause [2].…”
Section: Discussionmentioning
confidence: 99%